2020
DOI: 10.1182/bloodadvances.2020001608
|View full text |Cite
|
Sign up to set email alerts
|

Cold agglutinin–associated B-cell lymphoproliferative disease shows highly recurrent gains of chromosome 3 and 12 or 18

Abstract: Primary cold agglutinin disease (CAD) is a rare autoimmune hemolytic anemia caused by a distinct type of B-cell lymphoproliferative disease of the bone marrow. 1,2 We have recently evaluated the use of bendamustine-rituximab therapy for CAD and found that B cell-directed therapy is highly efficient and safe and may be considered first line therapy for relatively fit patients with CAD. 3 Hemolysis is mediated by binding of monoclonal immunoglobulin M antibodies (cold agglutinins) to the erythrocyte surface I an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…Next-generation sequencing of bone marrow B-cells revealed recurrent KMT2D and CARD11 gene mutations in CAD patients [61]. The findings of a current study using cytogenetic microarrays and exome sequencing allowed for the identification of highly recurrent increases of chromosomes 3 and 12 or 18 in CAD-associated lymphoproliferative disease [62]. Furthermore, these genetic features of chromosome instability were similar to those demonstrated in nodal and extranodal marginal zone lymphoma (MZL) [63].…”
Section: Pathogenesis Of Aihasupporting
confidence: 60%
“…Next-generation sequencing of bone marrow B-cells revealed recurrent KMT2D and CARD11 gene mutations in CAD patients [61]. The findings of a current study using cytogenetic microarrays and exome sequencing allowed for the identification of highly recurrent increases of chromosomes 3 and 12 or 18 in CAD-associated lymphoproliferative disease [62]. Furthermore, these genetic features of chromosome instability were similar to those demonstrated in nodal and extranodal marginal zone lymphoma (MZL) [63].…”
Section: Pathogenesis Of Aihasupporting
confidence: 60%
“…A recent study found trisomy 3 (+3 or +3q) in all of 12 samples from CAD patients who participated in a clinical trial. Nine of these had an additional trisomy 12 or 18, but never both (19). Malecka et al also found that the Ig light chain gene IGKV3-20 and, to lesser extent, the similar IGHV3-15 gene are used in most patients (74%) and might contribute to the I antigen binding.…”
Section: Origin Of Cold Agglutininsmentioning
confidence: 94%
“…There may be occasional cases with CA titer < 64 (3,16)." By definition, "patients may have a B-cell clonal lymphoproliferative disorder (LPD) detectable in blood or marrow but no clinical or radiological evidence of malignancy" (3), and there is evidence that CAD is a clonal LPD of the bone marrow in most, probably all cases (5,(17)(18)(19). This distinct clinicopathological entity should be called a disease, not syndrome (3,20).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike warm autoimmune hemolytic anemia, cold agglutinin disease (CAD) is a clonal hematologic disorder. Primary CAD is a distinct low grade lymphoproliferave disorder [ 31 , 32 , 33 ], with discernible histologic [ 31 ] and flow cytometric characteristics [ 32 ], immunoglobulin heavy and light chain gene features [ 33 ], cytogenetic abnormalities [ 34 ], and recurrent somatic mutations on next generation sequencing [ 35 ]. The pathogenic IgM is monoclonal, with kappa light chain specificity in 85% of cases [ 22 , 36 , 37 ].…”
Section: Aiha Pathophysiologymentioning
confidence: 99%